Interlaminar fracture toughness of CFRPs interleaved with stainless steel fibres. (15th February 2019) - Quan, Dong; Flynn, Stephen; Artuso, Marta; Murphy, Neal; Rouge, Clémence; Ivanković, Alojz
Abstract: Ductile stainless steel fibres were used as interlayers to enhance the interlaminar fracture toughness of carbon fibre reinforced plastics (CFRPs). The stainless steel fibres were placed at the mid-plane of CFRPs either longitudinally or transversely to the crack growth direction. Mechanical properties and fracture toughness of the CFRPs were studied using uniaxial tensile test and double cantilever beam test, respectively. The Young's modulus and tensile strength of CFRPs remained essentially the same due to the incorporation of steel fibres longitudinally to the loading direction, and decreased slightly for adding steel fibres transversely to the loading direction. Significant improvements in the fracture energy of CFRPs were achieved for adding stainless steel fibres, i.e. the mean fracture propagation energy increased from 482 J/m 2 for the control to 2295 J/m 2 for CFRPs with transverse steel fibres at a density of 320 filaments/mm. The main toughening mechanisms of the steel fibres were investigated to be extensive steel fibre bridging and tensile failure. A more pronounced toughness increment was observed for adding steel fibres transversely to the crack growth direction due to the additional mechanisms of carbon fibre delamination and breakage.